Pentecostalism: the relationship between interiority (bodies) and exteriority (dominion): Religion and Politics - Cascante, Luis Diego (2026)
The representation of the body in Costa Rican Pentecostalism (2016-2025) has two phases: the first, associated with evil before conversion and not aligned with asceticism against sin; the second, considered good if and only if the body is incorporated into the believing community -thanks to the Holy Spirit- which leads to a  resemanticization of the body (interiority) from the political body (exteriority) to unite religion and politics on the national political stage.